Microplasma assisted synthesis of gold nanoparticle/graphene oxide nanocomposites and their potential application in SERS sensing. (27th August 2019) - Sun, Daye; Tang, Miao; Zhang, Li; Falzon, Brian G; Padmanaban, Dilli Babu; Mariotti, Davide; Maguire, Paul; Xu, Heping; Chen, Mei; Sun, Dan
Abstract: This is the first study on the deployment of direct current atmospheric pressure microplasma technique for the single step synthesis of gold nanoparticle/graphene oxide (AuNP/GO) nanocomposites. The nanocomposites were characterized using ultraviolet–visible spectroscopy (UV–vis), x-ray diffraction and x-ray photoelectron spectroscopy and their formation mechanisms have been discussed in detail. Our AuNP/GO nanocomposites are highly biocompatible and have demonstrated surface enhanced Raman scattering (SERS) properties as compared to pure AuNPs and pure GO. Their potential as SERS substrate has been further demonstrated using probe molecules (methylene blue) at different concentrations.